Aktivitas Politik di Indonesia Dalam Pemikiran Islam (Studi Peran Ulama dalam Kontestasi Politik di Aceh Tenggara 2018-2019) - Adzan, Muhammad (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study explores the role of religious scholars (ulama) in the political contestation in Aceh Tenggara Regency in 2018. The research utilizes a qualitative exploratory method with a political approach to examine the influence of ulama in local elections and the community's response to their involvement. The findings reveal that ulama have a significant impact in mobilizing support for certain candidates. The community's response varies, ranging from strong support for ulama's political role to a preference for them to remain neutral. These findings highlight the close relationship between religion and politics in Aceh Tenggara and the important role of ulama in local political dynamics.